Propaganda Khilafah HTI di Indonesia - Ahmad Khotim Muzakka (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
This study presents contemporary issues related to khilÄfah or Caliphate (Islamic state) discourse in online media, http://hizbut-tahrir.or.id. The site is the official page of Hizbut Tahrir Indonesia (HTI). I am focusing on the contemporary issues discussed in this site. It is to find out what the theme of their discussion. The purpose of this study is to describe the construction of Caliphate discourse, especially in contemporary issues. Another purpose is to know the character of the Caliphate discourse used. The results of this study indicate that there are three main issues in hizbut-tahrir.or.id. First is regarded with the dangers of neoliberalism and neoimperalism. Second is on terrorism and violence. And third is on environmental issues. The character of Caliphate discourse; first is to use history as a religious legitimacy. And second is the exaggerated display of Islamic identity.